A bioinformatic approach of hydroxyapatite and polymethylmethacrylate composite exploration as dental implant biomaterial - Chiquita Prahasanti; Alexander Patera Nugraha; Viol Dhea Kharisma; Arif Nur Muhammad Ansori; Rini Devijanti Ridwan; Tansza Permata Setiana Putri; Nastiti Faradilla Ramadhani; Ida Bagus Narmada; I Gusti Aju Wahju Ardani; Tengku Natasha Eleena Binti Ahmad Noor (GarVal Editorial Ltda., 2021)
Context: The most common biomaterial used for dental implants is titanium. However, the release of metal ions and the risk of allergic reactions to metals that may occur in some patients cannot be avoided. Hydroxyapatite-polymethylmethacrylate (HA-PMMA) composite biomaterials are proposed to have potential as dental implant biomaterials due to their mechanical, chemical, and biological properties. HA-PMMA may induce osseointegration, biocompatible, less allergic reactions, and no metal ions released. In addition, HA-PMMA can be obtained from Indonesia's abundant natural resources. Aims: To explore HA-PMMA composites through molecular docking as a biomaterial candidate for dental implants in silico. Methods: Structure data format (sdf), molecular weight, and identity number (CID) of HA-PMMA ligand samples were obtained from PubChem database and minimized through OpenBabel. 3D structure, selection method, resolution, atom count, weight, sequence length, and ID protein BMP2, BMP4, BMP7, alkaline phosphatase (AP), osteonectin, osteopontin, and osteocalcin on RCSB-PDB native ligand and water sterilization on PyMol were carried out with the aim of to maximize the formation of binding affinity during molecular docking simulations. Results: HA-PMMA composites can enhance the activity of proteins associated with osseointegration such as BMP-2/4/7, AP, osteocalcin, osteonectin, and osteopontin in silico. HA-PMMA composites have the strongest binding to osteonectin and are predicted to enhance the AP activity in silico. Conclusions: HA-PMMA composites are potential candidates for dental implant biomaterials with the osteointegration ability through binding with BMP-2/4/7, AP, osteocalcin, osteonectin, and osteopontin in silico.